Resepsi Prinsip Childfree Dalam Tafsir Al-Qur’an: Kajian Kritikal Dan Interpretatif Terhadap Pemikiran Asma Barlas - Muhammad Abil Anam; Musfiroh, Mayadina Rohmi; Rosyada, Amrina (Muhammadiyah University of Surabaya, 2025)
This study examines how the childfree principle of the decision not to have children can be accepted or rejected from the perspective of the interpretation of the Qur'an through the thoughts of Asma Barlas. As a Muslim feminist, Barlas interprets the Qur'an by emphasizing gender equality and individual rights, and criticizes the patriarchal bias in traditional Islamic interpretation. Using a qualitative descriptive-analytical approach, this study discusses the interaction between the childfree principle and Islamic teachings on procreation and family. Through an analysis of relevant verses and Barlas's ideas, this study shows that the childfree decision can be seen as a legitimate personal choice as long as it considers social and ethical responsibilities. This study also assesses the implications of the childfree decision for spiritual and social values in Islam, and emphasizes the contribution of Barlas's thought in expanding the understanding of freedom and gender justice within the framework of the Qur'anic teachings. The significance of this research lies in its effort to enrich contemporary exegetical discourse with a contextual feminist perspective, opening a space for dialogue between modern individual values ​​and Islamic moral principles, and providing a theoretical basis for reinterpreting the role of women and the family in modern Muslim society. Keywords: Childfree, Tafsir Al-Qur'an, Asma Barlas.